Preparation and characterization of ceramic waste-based geopolymer ceramic composites for substrate culture application - Kannikar Kaewapai (2019)
© 2019 Trans Tech Publications, Switzerland. The present study focuses on the new application of geopolymer ceramic composites as substrate cultures, resulting from the geopolymer properties being similar to those of the substrate cultures such as water absorption, non-biodegradation, high porosity, and light weight. The geopolymers were synthesized from ceramic wastes and metakaolin using the geopolymerization method via a reaction with an alkaline solution. To compare usefulness for substrate culture applications, the porosity of different samples was varied. Moreover, the properties of all samples were investigated using an additional method of verification. The chemical characteristics were evaluated by FT-IR spectroscopy. The microstructures, pore sizes, pore distributions and surface areas of the pores were examined with image analysis using scanning electron microscopy (SEM). The densities were determined using the Archimedes' method. The porosity and water absorption were also measured. The mechanical properties were investigated by using a compression testing machine.